MONEY LAUNDERING WITH DRUGS PREDICATE CRIME STUDY OF COURT DECISION NO. 1243/PID.B/2012/PN.MDN. DATED 08 OCTOBER 2012 - Astri Heiza Mellisa; Bismar Nasution; Mahmud Mulyadi; Suhaidi Suhaidi (Universitas Sumatera Utara, 2014)
ABSTRACT Criminal sanction contained in Article 137 paragraph b. Act No. 35 of 2009 on Narcotics and Article 3 Jo. Article 2 (1) c. Act No. 8 of 2010 on the Eradiction and Prevention of Money Laundering, especially regarding imprisonment there are differences regarding liability, there is a lighter sentences in Article 137 paragraph b. Act No. 35 of 2009 that is at least 3 year and maximum 10 years in prison, while Article 3 Jo. Article 2 (1) of Act No. 8 of 2010, the criminal prison at most 20 years. Similarly, the sanctions imposed penalties, the Narcotics Act least Rp. 500.000.000,- (Five Hundred Million Rupiahs) and at most Rp. 5.000.000.000,- (Five Billion Rupiahs), while in the Anti Money Laundering Act a fine of Rp. 10.000.000.000,- (Ten Billion Rupiahs). On the one side, the Narcotics Act and Anti Money Laundering Act serves to combat criminal narcotics, but, on the other side, the Narcotics Act and Anti Money Laundering Act can use to lighter legal provisions to prosecute offenders. The problems that stand out in this study is how the reasoning of judges at first instance and appeal against money laundering predicate offenses with a crime associated with the narcotics Court Decision No. 1243/Pid.B/2o12/PN.Mdn., dated October 8th, 2012 that criminalized by Article 137 paragraph b. Act No. 35 of 2009, when according to the fact that unfold before trial, the accused can be punished with the provisions of Article 3 Jo. Article 2 (1) c. Act No. 8 of 2010. After doing some research, the conclusion found that the more specific provisions of law applicable when the legislators did intend to enforce the criminal provisions as a condition of a special nature. Associated with the court’s rulling, the judge has the right and correct in applying the law as lex specialis principle requires that law enforcement systematic use of more specific rules, such as Act No. 35 of 2009 about Narcotics.